Measuring the effectiveness of technology-based marketing strategies from the consumer perspective. Issue 6 (14th October 2019) - Fullerton, Sam; Brooksbank, Roger; Neale, Larry
Abstract : Purpose: Marketers are increasingly spoilt for choice as to which emerging technology to use for the purpose of enhancing their company's competitive advantage. Accordingly, there is an inherent need to assess, relative to the task of accomplishing an organization's marketing goals, the levels of consumer-perceived effectiveness germane to these options. Based on grounded theory, this study aims to develop an appropriate measurement instrument. Design/methodology/approach: Research is based on a survey featuring a cross-section of 18 technology-based initiatives that are being routinely incorporated within many companies' marketing strategies. A sample of 967 adult residents of the USA provided their perspective on the effectiveness of each initiative as a mainstream marketing tool. Findings: A wide spectrum of opinions exists as to what constitutes an effective initiative. Three sub-dimensions of the consumer-perceived effectiveness construct were identified and validated as measurement scales for use in future research: involvement stealth and outreach. Research limitations/implications: The generalization of the findings may be limited because minority segments of the adult American population, specifically, African Americans and Asian Americans were somewhat under-represented in the sample. Likewise, younger and older segments were slightly under- and over-represented, respectively. Practical implications: The study findings can be used to aid in the further development of an instrument designed to measure the strength and directionality of consumer-perceived marketing effectiveness. With the specter of an increasing array of technology-based strategic options going forward, using such an instrument will no doubt become a critically important success factor among business-to-customer (B2C) organizations. Originality/value: Few studies to date have sought to understand consumer perspectives regarding the effectiveness of technology-based initiatives as marketing tools, and none have explored the relativities of such perceptions across an array of different initiatives or examined any latent sub-dimensions of the construct. This study addresses these deficiencies.